THE EFFECTIVENESS OF THE JOLLY PHONICS METHOD ON LETTER RECOGNITION ABILITY IN 5-YEAR-OLD CHILDREN THROUGH LETTER CARD MEDIA - Yulva Mayarita; Prianggi Amelasasih; Yulyanto Yulyanto (Jurnal Impresi Indonesia, 2024)
Children aged 0-6 years are a fundamental educational period because development at this age determines development at the next age, which is determined by various stimuli provided from an early age. This research aims to determine the effectiveness of the jolly phonics method in improving the ability to recognize letters in five year old children using letter cards at TK X Surabaya. This type of research is experimental research in the form of Single Subject Research (SSR) using an ABAB design. The subject of this research was one of the TK X students in Surabaya. Data collection techniques in this research used pretest and posttest. The data obtained was analyzed using comparative descriptive. The results of the research show that the grades obtained by children have increased from before. At the first baseline the score was 2, and after the first intervention the child's score increased to 4. At the second baseline measurement the child obtained a score of 6, and after the second intervention the child's score increased to 8. Based on the research results, the use of the jolly phonics method is efficacious in improving children's letter recognition skills through letter cards for Kindergarten X Surabaya children.